PENGARUH ILUSTRASI DESAIN KEMASAN PADA PRODUK SINGKONG KEJU D-9 OLEH-OLEH KHAS KOTA SALATIGA - Ahmad Zainudin; Agus Priyadi; Dimas Pamungkas (STEKOM PRESS, 2021)
After doing research on Singkong Keju D-9 Salatiga, it can be seen that Singkong Keju D-9 Ready to Fried has limitations in its packaging, which is not yet in accordance with the regulatory standards of the State Ministry of Cooperatives and SMEs RI. In addition, it also has a packaging design that is not much different from competing products. Therefore, it is necessary to design a packaging design that is in accordance with the regulatory standards of the Ministry of Cooperatives and SMEs of the Republic of Indonesia and also innovation in packaging design that is able to provide characteristics as a souvenir product typical of the City of Salatiga so that it has an exclusive image on the product and continues to be able to compete against its competitors.The purpose of this study is to describe the effect of packaging design on consumer confidence in buying products based on packaging design and measure the accuracy of the theme of the illustration image on the packaging design of Singkong KejuD-9 as souvenirs typical of the city of Salatiga.The method used is the Research and Development method, starting with (1) potential and problems, (2) data collection, (3) packaging design, (4) packaging design validation, (5) packaging design revision, (6 ) product trials, (7) implementation.The results showed that the packaging design had met the requirements and met the requirements for use, judging from the results of the validation it had Cronbach's Alpha Reliability >=0.6 that the questionnaire used was very reliable.